The implications of latent technology regimes for competition and efficiency in banking - Michael Koetter; Tigran Poghosyan (Deutsche Bundesbank, 2008)
Banks continue to differ in many ways, for instance with respect to business models, growth strategies, or financial health. Neglecting these differences confuses inefficiency with heterogeneity while sub-sample estimation prohibits efficiency comparisons across different samples. We use a latent class stochastic frontier model to estimate simultaneously multiple technology regimes and group membership probabilities. The latter are conditioned on six bank traits of German banks and we identify four signifficantly different technology regimes. Only small, retail focused banks exhibit cost inefficiencies, which are 5.4% on average and thus substantially lower compared to previous studies. We use technology regime specific cost parameters to measure competition with Lerner indices. Large, national universal banks and the smallest, most specialized banks exhibit the lowest level of competition. In turn, medium sized universal banks are both efficient and exhibit the lowest Lerner margins between 1994 and 2004. – – Das deutsche Bankwesen wird oft als Drei-Säulen-System bezeichnet, welches aus Sparkassen, Geschäfts-, und Genossenschaftsbanken besteht. Diese Systematik wird oft als geradezu natürliche Marktsegmentierung verstanden. Banken können sich jedoch auch zwischen und innerhalb der drei Säulen hinsichtlich anderer Kriterien unterscheiden, zum BeispielWachstumsstrategien, Stabilitätseigenschaften oder Geschäftsmodellen. Viele vergleichenden Studien definieren oftmals vorab Teilstichproben, um diese Unterschiede zu berücksichtigen. Jede Bildung von Bankengruppen beinhaltet jedoch unweigerlich eine zum Teil willkürliche Komponente und verhindert außerdem den Vergleich relativer Effizienzmaße zwischen Teilstichproben. In dieser Studie benutzen wir ein latent class frontier model (LCFM), um unterschiedliche Technologiegruppen empirisch zu schätzen anstatt sie zu definieren. Wir ermitteln die Wahrscheinlichkeit der Gruppenzugehörigkeit (GZW) je Bank in Abhängigkeit von sechs individuellen Charakteristika. Für jede Technologiegruppe leiten wir Wettbewerbsma?e ab und untersuchen deren Entwicklung zwischen 1994 und 2004.
Keywords: G21; L1; 330; Banks; competition; efficiency; latent class frontier; strategy; Bank; Technische Effizienz; Bankensystem; Wettbewerb; Deutschland